The interplay of bureaucratic, humanistic work environment and organizational commitment - Apollo, Estrella; Acidera, Editha; Pellogo, Restita (Divine Word International Journal of Management and Humanities (DWIJMH) (ISSN: 2980-4817), 2024)
The study aimed to examine the interplay of bureaucratic, humanistic work environments and the organizational commitment of employees. To deepen the concepts of the study, literatures were reviewed. The study used a descriptive assessment and correlational research design. The population of the study were the employees of the Divine Word College of Laoag. To gather the data, validated questionnaires were used and weighted mean and Pearson r correlation were used to analyze the data. The findings indicate that the bureaucratic environment is higher than the humanistic environment which is at a moderate level and the organizational commitment of employees is also high. The correlation analysis demonstrates that there is no correlation between the bureaucratic, humanistic work environment and the organizational commitment of the employees. The higher organizational commitment is not caused by the work environment as suggested in the study, but it may be caused by other factors that are not considered in the current study. Thus, it is important to conduct other studies to investigate other factors like psychological factors and organizational factors that affect organizational commitment.